ANALISIS YURIDIS TENTANG KOMPETENSI RELATIF PENGADILAN HUBUNGAN INDUSTRIAL JAKARTA PUSAT COMPETENCY ANALYSIS OF CENTRAL JAKARTA INDUSTRIAL RELATIONS COURTS - Laila Rafida Rofi; Andari Yurikosari (Reformasi Hukum Trisakti, 2021)
An industrial relations dispute is a difference of opinion that results in conflict between employers or a combination of employers and workers/labor unions because of disputes regarding rights, interests, work relations and between work/labor unions. The industrial relations dispute that occurred between workers, namely Roy Sahata and PT Taruna Kusuma stated in the company regulations, namely in the Semarang court, however, the Central Jakarta Industrial Relations Court ruled that the Central Jakarta Industrial Court had the authority and examined the disputes that occurred.